1953
DOI: 10.1099/00221287-8-3-449
|View full text |Cite
|
Sign up to set email alerts
|

The Reproductive Pattern of Micromonospora vulgaris

Abstract: The thermophilic actinomycete Micrornonospora vulgaris resembles known mesophilic members of the genus Micromonospora in reproducing by means of small refractile spores borne singly on lateral branches of the vegetative mycelium.Its distinctive feature is the consistent production of a secondary aerial mycelium under optimal laboratory cultural conditions and in grass composts during the high temperature phase. This aerial mycelium is composed of abundantly branched, hydrophobic filaments which rapidly segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1955
1955
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…3 and 'nids', P h a u et al 1954). Such structures developed away from the glass as the growing filaments shifted direction slightly in accordance with the varying food supply, A photograph of such a ' loop ' produced under identical conditions to those described has already been published for Micromonospora vulgaris (Erikson, 1953: pl. 1, fig.…”
Section: Eriksonmentioning
confidence: 98%
“…3 and 'nids', P h a u et al 1954). Such structures developed away from the glass as the growing filaments shifted direction slightly in accordance with the varying food supply, A photograph of such a ' loop ' produced under identical conditions to those described has already been published for Micromonospora vulgaris (Erikson, 1953: pl. 1, fig.…”
Section: Eriksonmentioning
confidence: 98%
“…For example, the ability to utilize starch, which was previously not observed, is found in the description of Thermoactinomyces vulgaris of the 8th edition of the Manual (Ku$ ster, 1974). Kurup et al (1975) classified the isolates lacking amylase as Thermoactinomyces candidus and the isolates producing amylase as Thermo- Erikson (1953) as Micromonospora vulgaris strain D, which is listed as strain KCC A-0162 in the Approved Lists of Bacterial Names (Skerman et al, 1980). This strain corresponded to the original concept of Thermoactinomyces vulgaris by Tsiklinsky (1899) and the concept of Thermoactinomyces candidus.…”
Section: Thermoactinomyces Thalpophilus Kctc 9789mentioning
confidence: 99%
“…The flasks were set up in duplicate and examined daily for surface and bottom growth. Owing to the complex morphology of Micromonospora vulgaris (Erikson, 1953) it was not found possible to record the results of the growth experiments by conventional methods. Also, because of the inherent variability of a thermophil of such complexity of structure, it was found that not all the flasks gave uniform growth.…”
Section: H B M and F Of Micromonospora Vulgaris As Used By Eriksonmentioning
confidence: 99%
“…In this way little evaporation took place from the shallow liquid layer during the incubation period of 8-10 days at 58-60'. To ensure a water-saturated environment for maximum production of aerial growth (see Erikson, 1953) the side arms of the filter flasks were closed by means of short pieces of pressure tubing clipped with screw clamps. No evidence of limitation of growth by lack of oxygen was observed under these conditions.…”
Section: H B M and F Of Micromonospora Vulgaris As Used By Eriksonmentioning
confidence: 99%